ASPEK HUKUM PIDANA DALAM JASA PEMBUATAN TUGAS AKHIR MAHASISWA DI PERGURUAN TINGGI - Bella Maida Sasmita; Erdianto Effendi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The thesis jockey phenomenon occurs due to a combination of the education culture in Indonesia which is oriented towards the final grades and the mentality of the students themselves, plus the absence of firm regulations. The rise of thesis writing services in several cities is a serious challenge for existing universities. This practice is an act that can be said to be disgraceful or intellectual fraud.The purpose of this research is to find out how the aspects of criminal law are in the making of final assignments in higher education and how the criminal law policy towards final assignment making services in tertiary institutions for the future. The research method used in this thesis uses normative legal research methods, namely legal research that examines statutory regulations and legal principles.From the research, there are two main points that can be concluded. First, the aspect of criminal law in the services of making final assignments in tertiary institutions, namely that it cannot be included in the criminal act of fraud or contained in the Criminal Code because the elements of fraud are not fulfilled which for its perfection must have consequences. and one of them is due to the existence of the principle of legality in criminal law which states that a person cannot be convicted if there is no law that regulates it. Even though the act of making the final project is considered despicable, criminal sanctions cannot be given. Second, criminal law policy is an effort to make good criminal law regulations essentially inseparable from the goal of overcoming crime. In criminal law policy, the provision of crimes to tackle crimes is one of the efforts in addition to other efforts. The author's suggestion, First, it is hoped that the government will pay more attention to how the implementation of the world of education in Indonesia at this time, especially in universities by providing more specific arrangements regulating final assignment making services, and the campus should better monitor the process of making student final assignments, especially as supervisors. Second, it is hoped that the government can add to the thesis jockeying act in the National Education System Law and the Higher Education Law for academic fraud in addition to just plagiarism. Even if it cannot be changed or revised, it is hoped that there will be new regulations that specifically regulate the existence of legal certainty.Keywords: Juggling, Student Final Project, College, Criminal Aspects